KONTRIBUSI DAYA LEDAK OTOT TUNGKAI DAN KELENTUKAN OTOT PUNGGUNG TERHADAP KEMAMPUAN AKURASI SMASH TIM BOLA VOLI PADA KLUB PUTRA KANDIS JUNIOR KECAMATAN KANDIS KABUPATEN SIAK - Utami, Siti Kurniati; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on observations that the researchers saw during training and smash matches conducted at the junior kandis club, rarely did the players make sharp smashes so the results were not satisfactory, many players did smash shots that did not cross the net and the ball came out (most), most players kandis junior just smashes hard without thinking about placing the ball. The place of this research was conducted on the Jalan Datuh Syah andar volleyball court RT. 002 RW. 006 Simp. Belutu, Kandis District, Siak Regency. As for the population in this study are all research subjects, all junior volleyball athletes club kandis junior district Kandis siak district, which consists of 12 people. From the results of the study There is a significant relationship between Leg Muscle Explosion Power with the results of smash accuracy, where the rtab at a significant level α (0.05) = 0.602, means r count (0.9487)> rtab (0.602), There is a significant relationship between muscle flexibility back with the results of smash accuracy, where rtab at a significant level α (0.05) = 0.602 means r count (0.949)> rtab (0.602). There is a significant relationship together between the explosive power of the leg muscles and the flexibility of the back muscles with the results of the smash accuracy on the Kandis Junior club players, where the rtab at the significant level α (0.05) = 0.602, means Rhitung (0.9761)> rtab (0.602). In other words, it is concluded that Ha is accepted.Key Words: Leg Muscle Explosion Power of Back Muscle Detection Smash Accuracy Ability